Analisis Yuridis Putusan Hakim Pengadilan Negeri Lubuk Linggau Terhadap Pelaku Tindak Pidana Sumpah Palsu (Studi Putusan Nomor 464/Pid.B/2023/PN.Llg) - Rizal, M Ukbah; Supeno, Supeno; Razi, Fachruddin (Legalitas: Jurnal Hukum, 2024)
Perjury can occur both in court and outside of court. With regard to oaths, in reality, even though the name of God has been included, either as a guarantor of the truth of the information given or as a person who is asked for help so that the person concerned gives the actual information, there are still people who dare to give untrue information, especially if it is done under oath. In daily reality, many investigators often receive false reports or complaints from the public regarding a criminal offense. If a person gives a statement that has previously been sworn according to the method of his religion, but it turns out to provide untrue information or false information, then the person has committed a criminal act of perjury punishable in accordance with Article 242 paragraph (1) of the Criminal Code.